IMF Survey, Volume 35, Issue 19. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2006)
John Lipsky on IMF role; Liberia; Middle East outlook; Country briefs: Chile, Iceland; Ukraine reforms; Syria's oil crunch; Measuring sovereign risk; Maastricht inflation criterion; financial sector supervision; IMF bookstore; Nouriel Roubini.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet